A Study on SIM box or Interconnect Bypass Fraud - ALGHAWI, NAJMA (2019)
SIM box or Interconnect Bypass Fraud is one of the fastest emerging frauds in Telecom industry today, costing the industry some USD 3 Billion. Calls made through the internet are sent to SIM boxes (machines that contains SIM cards) which redirect this illegitimate VoIP traffic onto mobile networks. Fraudsters effectively bypass the inter-connect toll charging points to exploit the difference between the high interconnect rates and the low retail price for on-network calls, thus avoiding payment of the official call termination fee of an Operator or MVNO.